Meteorological condition and building effects on indoor/outdoor (I/O) air quality in London - Mohd. Aris, Mohd Shukri; Kelly, Frank; Barratt, Benjamin (2010)
The contributions of outdoor pollutant penetration and indoor sources have been proposed to be a major concern of the IAQ exposure. The concentrations of indoor contaminants are often higher than those found outdoors. The biologically relevant exposure time is seldom known, especially for mixtures as complex as those found indoors. Long-term continuous monitoring of gaseous pollutants is being carried out at adjacent internal and external sampling points at two diverse sites within London in order investigate the transport and chemical transformation of outdoor pollution indoors in both naturally and mechanically ventilated buildings. The findings from this study may potentially be used in the establishment of a London Indoor Air Quality Network The objective of the study was to monitor and analyse indoor/outdoor (I/O) data to assess the effects of meteorology, seasonality and building activity on the transfer of outdoor air pollutants into buildings with extremely diverse locations and use. Monitoring began in August 2008 and is ongoing. Site details are shown in Table 1. This part of the study investigated the influence of wind speed and direction conditions at each site. The effect of building closure was also investigated at the urban background school site. Analyses were carried out using the ‗openair‘ package within R statistical software (www.openair-project.org.uk).